Characterization of interface and grain boundary in Si3N4/SiC nanocomposites - Cheong, DS; Hwang, KT; Kim, CS (TRANS TECH PUBLICATIONS LTD, 1999)
Si3N4 composites reinforced with nano-sized SiC particles demonstrated distinguishable improvement of mechanical property at low and high temperatures. Especially Si3N4/20 vol% SiC with Y2O3 nanocomposites exhibited very high strength without degradation of strength at high temperatures to 1400 degreesC. Interface and grain boundary phase are major factors to control the high temperature strength of the nanocomposites like monolithic Si3N4. In these nanocomposites, characteristic of interfaces between Si3N4 and Si3N4 or SiC are varied mainly by sintering additive systems. A striking observation in these nanocomposites is that SiC particles at grain boundaries are directly bonded to Si3N4 grains without a glassy phase. Thus significant improvement of high temperature strength in these nanocomposites can be attributed to inhibition of grain boundary sliding and cavity formation primarily by intergranular SiC particles which are directly bonded to the matrix grains, besides crystallization of grain boundary phase. Rietvelt analysis of corresponding XRD diagram revealed that the secondary phase, h-pliase, 10Y(2)O(3).9SiO(2).Si3N4 and YSiO2N in samples With Y2O3, Y2O3 and Al2O3, respectively. The consistent results were obtained with TEM and HREM work.
Keywords: HIGH-TEMPERATURE STRENGTH; SILICON-NITRIDE CERAMICS; HOT-PRESSED SI3N4; BEHAVIOR; GLASS; PHASE; MICROSTRUCTURE; THICKNESS; SYSTEM; OXIDE